Mitochondrial Dynamics in the Drosophila Ovary Regulates Germ Stem Cell Number, Cell Fate, and Female Fertility - Garcez, Marcia (2021)
This project has received funding from the European Research Council (ERC) under the European Union’s Horizon 2020 research and innovation program (H2020-ERC-2017-STGGA 759853-StemCellHabitat), Wellcome Trust and Howard Hughes Medical Institute (HHMI-208581/Z/17/Z-Metabolic Reg SC fate), EMBO Installation grant (H2020-EMBO3311/2017/G2017), and by Fundação para a Ciência e Tecnologia (IF/01265/2014/CP1252/CT0004 and PD/BD/128003/2016 to MG).